The Empowerment through Femvertising: Reality or Myth? - Hernández Rodríguez, Tania Marcela; Sepúlveda Ríos, Irma Janett (Mercados y Negocios, 2022)
This article studied female empowerment and stereotypes through femvertising. Empowerment and stereotypes were characterized by the roles generated by the sexual division of labor, developing a qualitative analysis through the perception of young Mexican women. The challenges of this advertising strategy were identified as the role of messages and content. The results suggested the construction of new stereotypes without modifying the patriarchal structure.